Evidence of Wing Shape Sexual Dimorphism in Aedes (Stegomyia) albopictus in Mallorca, Spain - López-Mercadal, Júlia; Barretto Bruno Wilke, André; Barceló, Carlos; Miranda, Miguel Angel (Frontiers in Ecology and Evolution, 2021)
The Asian tiger mosquito Aedes albopictus (Skuse, 1894) is a highly invasive species widely distributed on the Spanish Mediterranean coast and the Balearic archipelago. Most studies involving this species in Spain have been focused on surveillance and control methods. However, micro-evolutionary studies for Ae. albopictus in Spain have been traditionally neglected. Morphological diversity could be the result of long-term evolutionary diversification in responses to selective pressures such as temperature, precipitation, food availability, predation, or competition that may influence flight activity, host-seeking, and blood-feeding behavior. Wing geometric morphometric have been used not only to study micro- and macro-evolution in mosquitoes but also in studies of population structuring and sexual dimorphism. Therefore, the main goal of this study was to investigate the wing shape patterns of Ae. albopictus populations to unveil sexual dimorphism that could provide information about their ecology and behavior. Mosquito eggs were collected using oviposition traps at the main campus of the University of the Balearic Islands (Palma de Mallorca, Spain) and reared under laboratory conditions. In order to study wing shape variation patterns in Ae. albopictus males and females, the left wing of each adult mosquito was removed and analyzed based on 18 landmarks. Our results indicated strong levels of sexual dimorphism between Ae. albopictus males and females. Furthermore, according to the cross-validated reclassification test, males were correctly distinguished from females with an accuracy of 84% and females from males 75%. We observed a significant sexual dimorphism in the wing shape patterns of Ae. albopictus when considering different seasonal patterns (spring vs. autumn). Our results suggested that selective pressures may affect males differently to females. Host-seeking, blood-feeding, and oviposition behavior of females may act as a major driver for wing shape sexual dimorphism. These results should be considered for the development of more effective and targeted mosquito control strategies.